Aquaculture Wastewater Treatment Using Constructed Wetlands Planted with Umbrella Palm (Cyperus alternifolius) - Phuong, Nguyen Minh; Thi Luu Ly, Hoang (VNU Journal of Science: Earth and Environmental Sciences, 2025)
Aquaculture in Vietnam plays an important role in the economy, however along with that is the problem of water pollution due to untreated wastewater. This study evaluated the capacity of constructed wetlands (CW) planted with umbrella palm (Cyperus alternifolius) using gravel, coconut fiber and Leca materials as substrate layers to treat aquaculture wastewater in Quang Ninh. The results showed that after 14 days, the wetland system planted with C. alternifolius on gravel and coconut fiber (CW1) and the wetland system planted with C. alternifolius using gravel and Leca (CW2) had good organic matter removal capacity with COD and BOD 5 reduction efficiency of over 82%, while the system using only gravel and coconut fiber (CW3) had COD and BOD 5 reduction efficiency of 71.6% and 75.9%, respectively; the system using only gravel and Leca (CW4) had COD and BOD 5 reduction efficiencies of 75.2 and 77.4%, respectively. After 14 days, the CW1 system had total suspended solids (TSS), ammonium (NH 4 + -N), nitrate (NO 3 - -N) and phosphate (PO 4 3- -P) removal efficiencies of 71.3%, 93.6%, 74.2% and 88.5%, respectively; meanwhile the TSS, NH 4 + -N, NO 3 - -N and PO 4 3- -P removal efficiencies in the CW2 system reached 76%, 87.7%, 68.5% and 92.8%, respectively. The research results showed the potential for applying constructed wetland systems planted with umbrella palm to treat aquaculture wastewater in Vietnam.